A Study Protocol for Checking Validity of Evaluation of Temporal Parameters of Gait Using Microsoft Kinect Azure in Normal Healthy Population - Jasraj Kaur Bhamra1 ,Waqar Naqvi1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: 5In healthy population, temporal parameters of gait like step time and stride time arefrequently linked with gait cycle in healthy populations but can be obstructive, difficult and time taking tomeasure. This study is to check the efficacy of kinect azure for evaluating of temporal parameters of gait innormal healthy people. A kinect based recording application was started & use to detect , tracks human postanalytical motions. Kinect is low cost, unobstructive and accurate gait analysis application with various useslike monitoring, diagnosis, rehabilitation & management. The end result of this study is to fed a state systemthat analysis the present state from which the assessment are withdrawn.Method: The research has been structured as an observational study. The total of 132 participants will betaken from AVBRH, sawangi Meghe for study as per inclusion and exclusion criteria. With intervention theperiod of study will be 6 months. It holds single period, concurrent validity evaluation comparing temporalgait parameters derived from the Kinect system.Discussion: This study protocol aims to evaluate the Validity of evaluation of temporal parameters of gaitusing Microsoft Kinect Azure. The study’s expected outcome will concert on the evaluation of temporalparameters of gait using Microsoft Kinect Azure in normal healthy population.